The Academic Failure among Students: Reasons and Recommendations - Alsulami, Adel Turki Saleh (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify the causes of academic failure among students of the Faculty of Arts and Human Sciences at King Abdulaziz University and to identify proposals to address the causes of academic failure among students of the Faculty of Arts and Human Sciences at King Abdulaziz University, and the researcher used the descriptive survey method, and the research community consists of students of the College of Arts and Human Sciences At King Abdulaziz University, whose rates are less than 2, and they are 52 students. The questionnaire was used to collect data from students, and the study concluded the following results: • Stumbling students seek more attention to the study. • There is a gap between the content of the study materials and the needs of students • The weakness of the college’s mentoring and mentoring process. • The certainty that there is no appointment or obtaining a job after graduation due to a large number of graduates. • Weak motivation and desire to study. In light of the results obtained, the researcher recommends the following: • Diversity in teaching methods. • Providing courses for students on how to obtain high scores in the subjects. • The importance of having a counselor in the department for students who are struggling. • The necessity to work on developing curricula in line with the needs of students • The necessity of having an academic advisor in the department for troubled students. • The need to reduce the number of students in one division.